ضمانات حقوق الإنسان في تعديلات قانون الإجراءات الجزائية الجزائري - مفتاح, عبد الجليل (revue mofakir; No 04 (2009): مجلـــة المفكــر, 2018)
ضمانات حقوق الإنسان في تعديلات قانون الإجراءات الجزائية الجزائري